PENGARUH CAPITAL ADEQUACY RATIO (CAR),LOAN TO DEPOSIT RATIO (LDR) DAN NET INTEREST MARGIN (NIM)TERHADAP RETURN ON ASSET (ROA) PADA PT. BANK TABUNGAN NEGARA (PERSERO) TBK PERIODE 2013-2023 - Risma Risiska, Reva; Khuzaeni (Journal of Research and Publication Innovation, 2024)
This study aims to determine how much influence Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) have on Return on Asset (ROA) of PT Bank Tabungan Negara Tbk in the period 2003-2023. The method used in the research is a descriptive quantitative method. Sampling using purpose sampling technique. The data analysis method used is simple linear regression analysis, multiple linear regression analysis, hypothesis testing T test, F test and coefficient of determination (R2) using the SPSS 25 approach. The population of this study is the annual financial report published by PT Bank Tabungan Negara Tbk. The T test results show that CAR has a Sig value. (0.457) > (0.05) and the value of t count < t table (-0.050) < (2.10982), this means that parisally CAR has no effect and is not significant on Return on Asset (ROA). LDR has a Sig. value (0.779) > (0.05) and the t value < t table (0.169) < (2.10982), this means that LDR partially has no effect and is not significant to Return on Asset (ROA). NIM has a Sig value. (0.082) > (0.05) and the value of t count> t table (3.659) > (2.10982), this means that NIM partially has a positive and significant effect on Return on Asset (ROA). While the results of the F-test research show that the value of Sig. (0.012) < (0.05) and the value of F count> f table 7.984> 3.01, this means that CAR, LDR and NIM simultaneously affect Return on Asset (ROA). The test results of the Coefficient of Determination (R2) show the Adjusted R-Square value of 0.677, this means that together the effect of CAR, LDR and NIM on Return on Asset (ROA) has a contribution of 67.7% while it is influenced by other variables not examined in this study.